Leon Battista Alberti and the Survey of the Walls of Rome (diségno, 2019)
The Descriptio Urbis Romae by Leon Battista Alberti represents the result of the first scientific survey of the city of Rome, of which however the author does not provide any data, but only some operational indications. The aim of this contribution is therefore the advancement of knowledge on the Albertian survey project, through the collection of direct clues, coming in particular from the reading of the Ludi mathematici, and the analysis of some singularities that can be deduced in the restitution. The study focuses in particular on the survey of the walls of Rome, an element of great importance in the Descriptio and which, due to its heterogeneity and territorial extension and the current persistence, is configured as a precious experimental opportunity. The restitution of the walls path, as it emerges from the graphic transcription of the numerical data present in the Alberti text, allows, compared with the current map, to produce new observations, crucial for the subsequent experiments, such as for example divergences of the walls and the coherence of the restitution for individual parts. By means of today’s digital simulation tools, designed to retrace a critical selection of the relevant experimental data produced by Alberti with the instruments of the time, and guided precisely by the observation of singularities, the research helps provide valuable clues on the original survey project.
Keywords: Descriptio Urbis Romae; urban survey; representation of the city; cartography; digital simulation